INVESTIGATION OF BIOPOLYMER-BASED KINETIC GAS HYDRATE INHIBITORS FOR FLOW ASSURANCE - YAQUB, SANA (2021)
In natural gas transmission pipelines, the formation of gas hydrate is a major flow assurance challenge, which chokes the pipeline, stops production and causes severe safety concerns. Currently used gas hydrate inhibitors are volatile, corrosive, and non-biodegradable. Biopolymers are reported as an efficient kinetic hydrate inhibitor (KHI). However, their biodegradability, influence on the hydrate phase equilibrium and the formation kinetics is still unmapped. This work aims to experimentally evaluate and compare the impact of biopolymers on the biodegradability, hydrate phase equilibrium and the formation kinetics. This study also seeks to predict the hydrate formation rate in the presence of biopolymers. The degradability extent of thirteen chemicals is investigated by measuring the ratio of biological oxygen demand and chemical oxygen demand.